Sistem Kehadiran Berbasis Web (Studi Kasus : Di PPKD Jakarta Pusat) - Yudi Aspuri; R. Tommy Gumelar; Elliya Sestri (ITB Ahmad Dahlan Jakarta, 2024)
The purpose of digitization is to make an institution or organization more effective and efficient in various aspects, one of which is attendance. Therefore, this research aims to design a digital attendance system using NodeMCU as the microcontroller and RFID (Radio Frequency Identification) as the sensor to read student ID cards, integrated with a web-based database. Currently, at PPKD (Pusat Pelatihan Kerja Daerah) Jakarta Pusat, the student attendance system still relies on conventional paper-based methods, which are ineffective, inefficient, and prone to errors. In addition to reducing paper usage, the design of this digital attendance system also aims to promote student discipline in attendance. The research employs the Research and Development (R&D) method, which aims to produce a specific product or enhance existing ones. The testing results demonstrate the successful transfer of student data from their ID cards (E-KTP) to the database via RFID sensors and NodeMCU microcontrollers. The system also displays this data on a web interface designed using PHP programming language. Overall, this research contributes to an effective and efficient attendance monitoring process for PIC (Person In Charge) at PPKD Central Jakarta